Photo-identification and the effects of tagging on the Patagonian catfish Hatcheria macraei - Barriga, Juan Pablo (2015)
Effects of subcutaneous visible implanted alphanumeric (VIA) microtags, pelvic fin excision, and individual photo-identification (Pid) based on natural spot patterns were experimentally evaluated in the small stream benthic Patagonian catfish Hatcheria macraei. VIA tag retention was 90 % during the first 45 days, decreasing to 80 % at day 200, and 66 % at the end of the experiment, at day 254. Fin regeneration was not evident during the experiment. Survival, growth rate or condition factor (Fulton’s K) did not differ between tagged or pelvic fin clipped catfish and a control group. Spot patterns varied greatly among individuals and remained constant throughout the experimental period, thereby making identification of individual Pid possible in H. macraei. Tagging was not effective in identifying individual fish due to mark loss or difficulty in reading VIA tag codes. The combination of Pid with VIA tagging or fin clipping techniques in longterm experiments is advisable in order to facilitate individual recognition. The Pid analysis described in this study is a low-cost method that could potentially be applied to any fish with a variable spot pattern.